Metacognition, study habits and attitudes - Gokhan ÖZSOY; Aysel MEMİŞ; Turan TEMUR (International Electronic Journal of Elementary Education, 2009)
This study is conducted to investigate the relationship between fifth grade students’ metacognition levels, and their study habits and attitudes. Participants of the study consist of 221 students, 125 female and 96 male, enrolling to six public primary schools in Turkey. The results revealed that there is a medium positive relationship between metacognitive knowledge and skills and study habits (r = .351, p < .05), study attitudes (r = .415, p < .05) and study orientation (r = .434, p < .05). Additionally, the results of the study showed that there is no significant relationship between metacognition and study habits and attitudes for low and medium achievers but, there is a significant relationship for high achievers.